Trinidad Carnival, Trinidad, W.I - Adams-Stayers (Adams-Stayers, 2009)
A group of carnival masqueraders wearing their colourful costumes.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Carnival; Carnival costumes